(untitled) - Keeble, David (London, 1976)
This book introduce approaches to industrial location analysis. Manufacturing location in the United Kingdom. The impact of industrial structure. Centre and periphery...
Keywords: Vị trí công nghiệp,Industrial location; Nước Anh,Great Britain